Design w kontekście zrównoważonego rozwoju i ergonomii – projekty Simo Heikkilä: Simo Heikkilä’s projects in the context of sustainable design and ergonomics - Wiśnicka, Anna (Artifex Novus, 2020)
Niniejszy tekst prezentuje wybrane projekty fińskiego designera Simo Heikkilä w kontekście zrównoważonego rozwoju, ekologii i regionalizmu oraz funkcjonalizmu i ergonomii. Wszystkie te kwestie stanowiły podstawę, na której oparta została jego filozofia projektowa. W swoich pracach Heikkilä odwoływał się do szeroko rozumianych idei ekologicznego designu, o czym świadczy wtórne wykorzystanie drewnianych odpadów przemysłowych, gloryfikacja patyny oraz filozofia wielopokoleniowego życia przedmiotów. Korzystając z lokalnie występujących materiałów oraz kultywując rzemieślnicze tradycje Północy wpisuje się również w nurt regionalizmu, który charakterystyczny jest dla designu fińskiego. Poszukiwania Heikkilä na arenie funkcjonalizmu oraz ergonomii, często twórczo połączone z ekologicznymi rozwiązaniami, pokazują potencjał tkwiący w designie skupionym na potrzebach użytkownika. Analizując przykłady projektów oscylujących wokół wyżej wymienionych zagadnień, artykuł prezentuje złożoną stylowo, acz wciąż koherentną, sylwetkę jednego z najbardziej cenionych fińskich projektantów. The article aims to focus on Simo Heikkilä’s projects in the context of sustainable design, functionalism and ergonomics – namely the three main fields of global research which determined his artistic activities. At the beginning the text provides a concise historical conditions and basic rules of questions regarding sustainable design, regionalism and ecological design, functionalism and ergonomics to serve as a background for any further deliberations on the matter. The very first question touched upon is sustainable design together with regional and ecologic approach. The strong bonds with nature, in Simo Heikkilä's case, were present in his praise for wood as well as for patina, manifested in various projects. Pieces such as Tupa or wood waste benches present the beauty of raw materials and wood’s endless possibilities. The idea was to design pieces which would recall the utilitarian concept of high quality in a simple form, suitable for mass production, which would serve for generations to come. Following comes the matter of ergonomics. Being a student of Yrjö Kukkapuro, Heikkilä had a chance to see how the principles of ergonomics were put into practice. The simplicity of form, suitable for the office environment, was linked with carefully designed backrests and armrests which provided the user with a comfortable work position. The most vivid example of the search for the ergonomic solution in Heikkilä's works were all the versions of the Divaani chaise longue. It was the quintessence of ergonomic design, as it had derived straight from the shape of the human body, underlining the connotation with an anthropomorphic shape. His experiments with various components resulted in different effects, from very organic ones, which combined natural materials such as wood or rattan with the shape or contrasting the form with such a cold material as steel. Regardless the final effect, the basic concept inspired by the shape of the human body made the project deeply rooted in nature, which was typical of many Heikkilä's projects. Simo Heikkilä's style in terms of furniture design is a very distinctive one, however, it had been influenced by his origins, provenance, education, and both national and world-wide achievements. He intuitively combined local materials and evanescent techniques of local craftsmen, which were part of his earliest art-related memories with innovative ideas introduced by modernism. Hence, in his projects materials such as wood, plywood and steel, often combined with each other for a strong stylistic effect, can be seen. The forms he used were simple, underlining the basic construction ideas, as it can also be considered a part of the design. All of the factors, in combination with Simo Heikkilä's design rules regarding ecology, recycling and regionalism, make his projects unique on the scene of contemporary industrial design.